Construction how to play rational in Physical Education classes - Costa, Andrize Ramires; Barros, Thais Emanuelle da Silva; Kunz, Elenor (Motrivivência, 2018)
In this essay we bring main focus is the child who always has great pleasure in “Selfmovement”. The basis for his “Self- movement” is the natural need of the child to play. It turns out that the natural tendency of “ If jogging “ and play the child quickly turns into social and cultural activity by the appropriation of elements of the culture and environment that arise by induction, for the most part , by the imposition of adults accepted activities and recognized by them, finalized pointing Physical Education which often do not allow their own experiences children movement , play and for games of a movement “right “ pregiven and created by third parties, to meet future development undertakings by often one of the most alienating and castrating experiences of freedom and human creativity.